Healthcare Workers (HCWs)’ Perceptions and Current Practice of Managing Cognitively Impaired Patients with Chronic Obstructive Pulmonary Disease (COPD) - Rayan A. Siraj (Medicina)
Background and Objectives: Despite the significant impacts of cognitive impairment on patients with chronic obstructive pulmonary disease (COPD), there is limited information available on healthcare workers’ (HCWs) perceptions, current practice, and barriers to managing COPD patients with cognitive impairment. Materials and Methods: A cross-sectional questionnaire was distributed to HCWs in Saudi Arabia between April and December 2023. The collected responses were analysed using descriptive statistics and logistic regression models. Results: A total of 890 participants, including nursing, physical, and respiratory therapists, completed the online questionnaire. Over two-thirds of the study participants indicated not having sufficient knowledge or adequate training in managing cognitive impairment in patients with COPD. The majority of HCWs perceive cognitive impairment to underdiagnose COPD (83%), underestimate COPD severity (81%), exacerbate COPD symptoms (80%), and interfere with self-management (81%) and pulmonary rehabilitation (81%). However, less than 45% (n = 394) reported having the potential to recognise signs of cognitive impairment during patient encounters. Logistic regression analysis revealed that male healthcare practitioners were more likely to recognise cognitive impairment than females (OR: 1.48; 95% CI: 1.13 to 1.95; p < 0.001). Physical and respiratory therapists were more likely to identify cognitive impairment compared to nurses. Additionally, having more years of experience (≥10 years, OR: 1.63; 95% CI: 1.02 to 2.61; p = 0.001) and adequate knowledge of cognitive impairment (OR: 6.23; 95% CI: 4.18 to 9.29; p = 0.001) were strongly associated with better recognition. Confidence in managing cognitively impaired COPD patients was low, attributed to poor training (64%), inadequate knowledge (64%), and the absence of standardised procedures (58%). Conclusions: HCWs agreed upon the negative impacts associated with cognitive impairment in patients with COPD. However, the potential of recognising signs of cognitive impairment and confidently dealing with the existence of cognitive impairment in COPD is not optimal, owing to poor training and limited knowledge. A focus should be given to managing comorbidities alongside COPD.